A semiformality of micro-enterprises. The case of Brunca Region, Costa Rica - Abarca-Jiménez, Geovanny (2019)
The article addresses the phenomenon of semiformality that affects the microenterprise units operating in the Brunca Region of Costa Rica. To determine this, we focused on the requirements that these type of companies must meet, in accordance with Costa Rican legislation, to be subject to credit through the Banca para el Desarrollo programs. The variables studied include: their legal status related to the Direct Taxation Office, being registered as employers in the Costa Rican Department of Social Security, and having the municipal permit up to date. These variables are weighted and compared with the indicators of competitiveness of each area studied. The study determined a high level of semiformality in the microenterprise sector, but it was less than at national level. It is concluded that, given the social and economic conditions of this region, the phenomenon of informality seems to be a strategy to survive in areas with low access to sources of employment, and high social and economic vulnerability.